Pengaruh Faktor Internal Perusahaan Terhadap Pengungkapan Aset Biologis Pada Perusahaan Agrikultur - Karen Aurelliza; Elsa Imelda (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The purpose of this study is to analyze the effect of biological asset intensity, profitability, company size, and ownership concentration on biological asset disclosure based on PSAK 241 in agricultural companies listed on the IDX, with 18 agricultural companies for the period 2018-2022 obtained through purposive sampling techniques. The findings of the study indicate a significant positive effect between biological asset intensity and ownership concentration on biological asset disclosure, which means that the company's commitment to disclosing biological assets in its annual report will increase along with the number of biological assets owned and ownership concentration.